A very sensitive flow-injection spectrophotometric determination method for iron (II) and total iron using 2′, 3, 4′, 5, 7-pentahydroxyflavone - Asan, Adem; Aydin, Rukiye; Semiz, Deniz Karsli; Erci, Vildan; Isildak, Ibrahim (SPRINGER, 2013)
In this study, an ultra-sensitive and highly selective, rapid flow-injection spectrophotometric method for the determination of iron (II) and total iron has been proposed. The method was based on the reaction between iron (II) and 2', 3, 4', 5, 7-pentahydroxyflavone in slightly acidic solution with a strong absorption at 415 nm. The carrier solution used was 1 x 10(-5) M 2', 3, 4', 5, 7-pentahydroxyflavone in 0.1 M HAc/Ac- buffer solution at pH 4.5. Parameters that affect simultaneously the determination of iron (II) and interfering ions were tested. The relative standard deviation for the determination of 50 mu g L-1 iron (II) was 0.85 % (n = 10), and the limit of detection (blank signal plus three times the standard deviation of the blank) was 3 mu g L-1, both based on injection volumes of 20 mu L. The method has been successfully applied to the determination of iron (II) and total iron in water samples and ore samples. The method was verified by analysing a certified reference material Zn/Al/Cu 43XZ3F.
Keywords: Flow-injection analysis; Iron; Spectrophotometry; 2 ', 3, 4 ', 5, 7-Pentahydroxyflavone; WATER SAMPLES; IRON(III); ACID; FE(III); PRECONCENTRATION; SPECIATION; FERROZINE; SEAWATER; RESIN; Environmental Sciences & Ecology